2005
DOI: 10.1021/es0508166
|View full text |Cite
|
Sign up to set email alerts
|

Plant Uptake of Non-Ionic Organic Chemicals

Abstract: Plant uptake of organic chemicals is an important process when considering the risks associated with land contamination, the role of vegetation in the global cycling of persistent organic pollutants, and the potential for industrial discharges to contaminate the food chain. There have been some significant advances in our understanding of the processes of plant uptake of organic chemicals in recent years; most notably there is now a better understanding of the air to plant transfer pathway, which may be signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
355
2
16

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(391 citation statements)
references
References 84 publications
18
355
2
16
Order By: Relevance
“…If only the process of uptake occurs, the parent and metabolite concentrations in plants should finally approach equilibrium. 36 However, results of this study showed that levels of 8:2 FTOH, 8:2 FTCA, 8:2 FTUCA, and 7:2 sFTOH in different soybean tissues clearly decreased after reaching a peak level. These patterns indicated that 8:2 FTOH could be degraded to intermediates and further to stable degradation products in soybean.…”
Section: ■ Materials and Methodscontrasting
confidence: 63%
“…If only the process of uptake occurs, the parent and metabolite concentrations in plants should finally approach equilibrium. 36 However, results of this study showed that levels of 8:2 FTOH, 8:2 FTCA, 8:2 FTUCA, and 7:2 sFTOH in different soybean tissues clearly decreased after reaching a peak level. These patterns indicated that 8:2 FTOH could be degraded to intermediates and further to stable degradation products in soybean.…”
Section: ■ Materials and Methodscontrasting
confidence: 63%
“…Plants play an important role in the terrestrial ecosystem. The uptake and metabolism of organic contaminants in the environment frequently occurred in plants and represent the first step of the food chain (Collins et al, 2006). Plant uptake of PBDEs was already observed (Tian et al, 2012), however, there have been few studies on the fate of OH-PBDEs and MeOPBDEs in environmental plants.…”
Section: Introductionmentioning
confidence: 99%
“…29 The most likely hypothesis of POPs accumulation is the direct transport from the roots to the xylema through apoplastic and symplastic movement and subsequent translocation to other organs, similarly to water and nutrient absorption. 30 Naturally, non polar pollutants can be solubilized in water and absorbed by plants. Matsumoto et al 31 proposed that root eliminated compounds of low molecular weight, such as citric acid, organic acids and proteins can increase POPs solubility.…”
Section: Phytoremediation Using Sunflowermentioning
confidence: 99%